The Achievement of Minimum Service Standards for Newborns at Bukitsangkal Health Center 2024 - Farhana, Salwa; Jasmine, Annisah Biancika; Putri, Rachelia Anugerah; Azzahra, Nayla Khanisa; Nurrohima, Meiliza; Ulfa, Siti Zahara Nur Khatimah; Amalia, Riski; Harmadi, Harmadi; Marheini, Hilda; Hertanti, Ferra (Universitas Ibn Khaldun Bogor, 2025)
This study aims to analyze the achievement of Minimum Service Standards (MSS) for newborns at BukitSangkal Health Center in 2024, based on the importance of meeting MSS in improving maternal and newborn health quality. The methodology used was a descriptive research design with a cross-sectional approach, where data were collected through a recapitulation of newborn services at BukitSangkal Health Center. The study population included all registered newborns, with a sample of 458 babies who received services according to standards. The results showed that BukitSangkal Health Center achieved 100% of SPM targets. Out of 458 infants, 215 were male, and 207 were female, with a balanced distribution. Hepatitis B0 and BCG immunization coverage also showed satisfactory results. The availability of quality goods such as vaccines and MCH books reached 100%, but the quality of health human resources (HRH) still needs to be improved, with only a percentage of 51.9%. Overall, the quality of basic services reached 75.95%. This study emphasizes the need for more attention to human resources aspects to maintain service quality and ensure newborns receive optimal care. These results are expected to be a reference for related parties to improve health service standards at the Public Health Center and other health facilities.